ANALISIS SISTEM PENERAPAN E-FAKTUR DALAM PELAPORAN SPT MASA PPN PADA PT. KAYABA INDONESIA - Kharisma Yulia Bellanty, (2022)
e-Invoice is an electronic tax invoice created by the Directorate General of Taxes as an effort to reduce the number of cases of issuing fictitious tax invoices. The implementation of the e-Invoice application was carried out in stages starting July 1, 2014, July 1 2015, and July 1, 2016. This study was conducted to analyze the application of the e-Invoice system in reporting the Periodic Value Added Tax Return at PT. Indonesian Kayaba. The research method used is a qualitative research method with a case study approach. The results showed that PT. Kayaba Indonesia has implemented the e-Invoice application since July 1, 2016. The application of the e-Invoice system PT. Kayaba Indonesia has been running in accordance with the regulations set by the Directorate General of Taxes. PT. Kayaba Indonesia has also never been late in reporting the Periodic Value Added Tax Return, although some corrections have been found for several tax periods. In addition, the obstacles that occur when implementing e-Invoice are the dependence of the e-Invoice system with the internet network and the amount of memory when backing up data.